2021
DOI: 10.1371/journal.pone.0257594
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia increases the risk of post-operative recurrence in patients with non-small cell lung cancer

Abstract: Background Sarcopenia is among the most prevalent and serious cancer-related symptom, and is strongly correlated with a poor prognosis. Moreover, it reportedly predicts poor prognosis after surgery in patients with lung cancer. However, it is unclear whether sarcopenia directly affects post-operative recurrence. The purpose of this study was to evaluate whether sarcopenia can be a risk indicator for post-operative recurrence, and whether it suppresses anti-tumor immunity, in a cohort of patients with resected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Kawaguchi et al showed that patients with NSCLC and sarcopenia had larger tumors and lymph nodes and more extensive vascular invasion than patients without sarcopenia, which is consistent with our ndings(Kawaguchi et al 2021). Sarcopenia can be divided into ''primary'' or agerelated sarcopenia when no other cause is evident other than aging itself, or ''secondary'' when one or more causes can be identi ed (Cruz-Jentoft et al 2010;Williams et al 2021).…”
supporting
confidence: 93%
“…Kawaguchi et al showed that patients with NSCLC and sarcopenia had larger tumors and lymph nodes and more extensive vascular invasion than patients without sarcopenia, which is consistent with our ndings(Kawaguchi et al 2021). Sarcopenia can be divided into ''primary'' or agerelated sarcopenia when no other cause is evident other than aging itself, or ''secondary'' when one or more causes can be identi ed (Cruz-Jentoft et al 2010;Williams et al 2021).…”
supporting
confidence: 93%
“…This was also a strong negative predictor in patients with lung cancer undergoing surgery (32). Recent publications mentioned a significant correlation between sarcopenia and lower oncological survival (cancerspecific and recurrence-free survival) among patients undergoing lung cancer surgery, which supports our results (33,34). Therefore, lower BMI, reflecting sarcopenia, was notable among octogenarians; an interventional approach, including perioperative positive nutritional support and © Current Challenges in Thoracic Surgery.…”
Section: Comparison With Similar Researchessupporting
confidence: 85%
“…Sarcopenia has a high impact on public health because it is associated with many comorbidities, such as osteoporosis [ 37 ]. One cohort demonstrated sarcopenia as a high risk factor for lung cancer recurrence, and also the tumours of patients with sarcopenia have higher malignant potential [ 13 ]. Imaging evaluations such as CT are considered to be the gold standard for its diagnosis, and they reduce the need for another test, but other modalities, such as DXA, are often preferred owing to their lower costs [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other smoking-related diseases also identified in LCS studies and associated with lung cancer such as hepatic steatosis and sarcopenia were also considered in this study [ 12 , 13 ]. Sarcopenia is characterised by the loss of muscle mass and function and affects mainly elderly adults, such as those participating in our study [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%